IoT Community Technologies: Leaving Users to Their Own Devices or Orchestration of Engagement? - Balestrini, M.; Diez, T.; Marshall, P.; Gluhak, A.; Rogers, Y. (EAI Endorsed Transactions on Internet of Things, 2015)
Citizens are increasingly crowdfunding IoT based participatory sensing technologies that allow them to collect and share data about the environment. These initiatives are usually referred to as grassroots and are driven by a vision of widening access to tools for political action. In this paper we compare patterns of participation and user experience over 15 months in two distinct communities using ‘Smart Citizen’, a crowdfunded IoT participatory sensing tool. Our studies reveal that technology issues and a lack of reliability of the sensed data hindered user participation. However, in one of the communities, many of these challenges were overcome through orchestrated actions led by community champions. We discuss how crowdfunding doesn’t necessarily translate into active participation and provide guidelines on how to achieve sustained engagement in crowdfunded IoT community sensing projects: enable distributed orchestration provided by local champions, encourage social interactions that embed skills and learning, and facilitate meaningful participation and reward mechanisms among community members.
Keywords: IoT community technologies; engagement; crowdfunding; social action; activism; participatory sensing